2021
DOI: 10.12973/eu-jer.10.2.671
|View full text |Cite
|
Sign up to set email alerts
|

Research-Oriented Framework of Training Philology Students’ Research Skills Based on Corpus Analytical Software

Abstract: <p style="text-align: justify;">The purpose of the study was to explore how technological advances incorporated into the Philology Studies curriculum could impact the students’ research skills and the quality of their research projects and what students’ and teachers’ impressions of the reshaped research component of the curriculum were. The study used qualitative and quantitative methods with the dominance of qualitative methods. It employed the baseline study, checklist to assess students’ research pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…Teacher's ranking is less important. According to other researchers [3], [29], [30], the essential skills in teachers' work are the ability to explain the material and train the necessary skills in students. A total of 93% of teachers consider it necessary to engage in selfeducation to be competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher's ranking is less important. According to other researchers [3], [29], [30], the essential skills in teachers' work are the ability to explain the material and train the necessary skills in students. A total of 93% of teachers consider it necessary to engage in selfeducation to be competitive.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the teaching method which involves mind maps (for example, presentation of lecture material or the results of independent work) is more effective than traditional teaching methods (Bawaneh, 2019;Yang et al, 2022;Valyukevych et al, 2021). The lack of works dealing with the effectiveness of the mind maps for students of the Humanities majors was mentioned above.…”
Section: Literature Reviewmentioning
confidence: 97%
“…La muestra más grande es la de 867 profesores universitarios del sistema educativo español (Guillén-Gámez et al, 2020). Luego se tiene la muestra de 531 profesores y estudiantes de la Facultad de Educación de la UNED de Costa Rica (Ávalos et al, 2019) y, la muestra de 287 estudiantes de una universidad de Ucrania (Valyukevych et al, 2021). Para el caso de los estudios cualitativos destacan 29 profesores en formación (Wongdee, 2019), 27 profesores (González- Guerrero et al, 2017), 19 profesores de Química en formación (Oner et al, 2011) y 3 profesores de la Universidad de Cambridge (Hennesy et al, 2011).…”
Section: Caracterización Descriptiva De Las Publicacionesunclassified
“…Unas clásicas y otras más innovadoras. Para el primer caso se propone el aprendizaje basado en problemas, en la práctica, en la reflexión, en la indagación, porque se considera que favorecen los resultados académicos de los estudiantes (Valyukevych et al, 2021) y el aprendizaje experiencial y realista que promueve la resolución de problemas (Ávalos et al, 2019).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation